13.3‐inch 8k4k 664‐ppi foldable OLED display using crystalline oxide semiconductor FETs. Issue 12 (2nd December 2015) - Takahashi, Kei; Sato, Takehisa; Yamamoto, Roh; Shishido, Hideaki; Isa, Toshiyuki; Eguchi, Shingo; Miyake, Hiroyuki; Hirakata, Yoshiharu; Yamazaki, Shunpei; Sato, Rai; Matsumoto, Hironori; Yazaki, Naomi
Abstract: A prototype 13.3‐inch 8k4k 664‐ppi high‐resolution foldable organic light emitting diode display is constructed. C‐axis aligned a‐b‐plane‐anchored crystal In–Ga–Zn oxide field effect transistors designed using a 1.5‐µm rule process are used in the backplane. Each pixel circuit has three transistors and one capacitor, and an external circuit is used to correct pixel current. Abstract : We fabricated a prototype 13.3‐in 8k4k 664‐ppi high‐resolution foldable organic light‐emitting diode display. C‐axis aligned a‐b‐plane‐anchored crystal In–Ga–Zn oxide field effect transistors designed using a 1.5‐µm rule process are used in the backplane. Each pixel circuit has three transistors and one capacitor, and an external circuit is used to correct pixel current.